Faktor-Faktor yang Mempengaruhi Pelaksanaan Amalan Perhubungan Pekerjaan di Perusahaan Kecil Dan Sederhana (PKS): Satu Tinjauan Literatur - Noor Syakirah Zakaria; Mohd Khairuddin Hashim (2016)
The existence of Small and Medium Sized Enterprises (SMEs) has been proven to have significantly contribute d to improving nation’s economic development particularly in creating abundant job opportunities. Nonetheless, past studies also revealed that the SMEs had to confront various challenges including the task of ensuring their continuous survival. Therefore, in order to sustain their existence, previous researches had suggested that the SMEs must seek to establish commendable employer employee relationships. Having said so, they also acknowledged that the task was not without its difficulties. Review of past l iterature showed that there were vario us factors that influenced the relationship between employer employee. Based on review of past literature, this article explores and examines the factors that give effects to good working relationship practice in the context of SMEs.